Simultaneous Measurements of PM2.5- and PM10-bound Benzo(a)pyrene in a Coastal Urban Atmosphere in Poland: Seasonality of Dry Deposition Fluxes and influence of Atmospheric Transport - Patrycja Siudek; Wiesława Ruczyńska (Aerosol and Air Quality Research)
Abstract Parallel 24-h measurements of PM2.5- and PM10-bound benzo(a)pyrene (BaP) were conducted in a coastal urban region in northern Poland in 2019. The aim was to examine distribution profiles, dry deposition fluxes and perform a trajectory analysis to investigate potential source regions of pollutants. The mean ratio of PM2.5/PM10 was 0.70 ± 0.23, suggesting significant heterogeneity in PM composition during the study period, both in fine and coarse fraction. The measurements revealed a strong seasonal variation in the concentration and dry deposition fluxes of BaP. The peak BaP concentrations of 6.14 ng m–3 and 6.65 ng m–3, respectively in fine and coarse PM fractions were observed in December. They were directly attributed to local emission from major industrial (i.e., coal-fired power plants, refinery, solid waste burning, metal recycling plants) and residential sources (domestic heating units), and to the meteorological situation that led to the reduced dissipation of air pollutants and their transport outside the study domain. During the period from October to November, high Pb/Zn ratios in PM2.5 and PM10 were also observed, suggesting significant contribution of industrial emission (coal combustion) and local non-exhaust traffic emissions, including tyre abrasion in the case of Zn and the resuspension of road dust rich in Pb. The highest daily BaP deposition fluxes of 2652 ng m–2 (PM2.5) and 5561 ng m–2 (PM10) were reported in winter, while the lowest values of daily BaP deposition (2 ng m–2) were found during spring and summer measurements. Additionally, the three-dimensional FLEXTRA transport model was used to identify the impact of different sources on air masses over the study domain. FLEXTRA results showed that the air masses transported from distant S to W regions greatly affected the chemical composition of PM2.5 and PM10 during autumn and winter.